Energy and thermodynamic performance of refrigerator using pure hydrocarbon and mixture of hydrocarbons as refrigerants - Sattar, M.A.; Saidur, R.; Masjuki, H.H.; Mohiuddin, A. K. M. (2007)
This paper presents an experimental investigation on the performance of a domestic refrigerator using pure butane and mixture of propane, butane and isobutene as refrigerants. The experiment was conducted with a refrigerator designed to work with HFC-134a under the same no load condition at a surrounding temperature of 25°C and 28°C. The refrigeration capacity, the compressor power, the coefficient of performance (COP), condenser duty and heat rejection ratio were investigated. It can be stated that the performance of butane is comparable with the performance of the HFC134a. The result shows a better performance of butane than HFC-134a. The results support the possibility of using butane as an alternative to HFC134a in domestic refrigerators without any modification of the domestic refrigerator.